Matrix Metalloproteinase-2 Impairs Homing of Intracoronary Delivered Mesenchymal Stem Cells in a Porcine Reperfused Myocardial Infarction: Comparison With Intramyocardial Cell Delivery - Zlabinger, Katrin; Lukovic, Dominika; Hemetsberger, Rayyan; Gugerell, Alfred; Winkler, Johannes; Mandic, Ljubica; Traxler, Denise; Spannbauer, Andreas; Wolbank, Susanne; Zanoni, Gerald; Kaun, Christoph; Posa, Aniko; et al. (Frontiers in Bioengineering and Biotechnology, 2018)
Background. Intracoronary injection of mesenchymal stem cells (MSCs) resulted in a prompt decrease of absolute myocardial blood flow (AMF) with late and incomplete recovery of myocardial tissue perfusion. Here we investigated the effect of decreased AMF on oxidative stress marker matrix metalloproteinase-2 (MMP-2) and its influence on the fate and homing and paracrine character of MSCs after intracoronary or intramyocardial cell delivery in a closed-chest reperfused myocardial infarction model in pigs. Methods. Porcine MSC were transiently transfected with Ad-Luc and Ad-GFP. One week after MI, the GFP-Luc-MSCs were injected either intracoronary (group IC, 11.00±1.07 x106) or intramyocardially (group IM, 9.88±1.44 x106). AMF was measured before, immediately after, and 24h post GFP-Luc-MSC delivery. In vitro bioluminescence signal was used to identify tissue samples containing GFP-Luc-MSCs. Myocardial tissue MMP-2 and CXCR4 receptor expression (index of homing signal) were measured in bioluminescence positive and negative infarcted and border, and non-ischemic myocardial areas one-day post cell transfer. At 7-day follow-up, myocardial homing (cadherin, CXCR4, SDF-1alpha) and angiogenic (FGF2, VEGF) were quantified by ELISA of homogenized myocardial tissues from the bioluminescence positive and negative infarcted and border, and non-ischemic myocardium. Biodistribution of the implanted cells was quantified by using Luciferase assay and confirmed by fluorescence immunochemistry. Global left ventricular ejection fraction was measured at baseline and one-month post cell therapy using MRI. Results. AMF decreased immediately after intracoronary cell delivery, while no change in tissue perfusion was found in the IM group (42.6±11.7 vs. 56.9±16.7 ml/min, p=0.018). Intracoronary delivery led to a significant increase in myocardial MMP-2 64 kD expression (448±88 vs. 315±54 intensity*mm^2, p=0.021), and decreased expression of CXCR4 (592±50 vs. 714±54 pg/tissue/ml, p=0.006), with significant exponential decay between MMP-2 and CXCR4 (r=0.679, p<0.001). FGF2 and VEGF of the bioluminescence infarcted and border zone of homogenized tissues were significantly elevated in the IM goups as compared to IC group. LVEF increase was significantly higher in IM group (0.8±8.4 vs 5.3±5.2 %, p=0.046) at the 1-month follow up. Conclusions. Intracoronary stem cell delivery decreased AMF, with consequent increase in myocardial expression of MMP-2 and reduced CXCR4 expression with lower level of myocardial homing and angiogenic